The iPhone photography book : how to get professional-looking images using the camera you always have with you - Kelby, Scott (Rocky Nook, 2021)
An award-winning photographer, in this long-awaited book fully dedicated to iPhone photography, shares his secrets and shooting advice for capturing truly amazing pictures with an iPhone.